REFUSAL STRATEGIES USED BY MALE AND FEMALE STUDENTS OF ENGLISH LITERATURE IN CAMPUS SETTING OF UNIVERSITAS BRAWIJAYA - FITRIANA, EKA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: refusal, refusal strategy, gender, campus setting. This study aims to find out refusal strategies used by male and female students of English Literature, Universitas Brawijaya. There are two problems of the study: (1) what the types of refusal strategies used by male and female students of English Literature in campus setting of Universitas Brawijaya are, and (2) what possible factors that influence the differences of the use of refusal strategies by male and female students of English Literature in campus setting of Universitas Brawijaya are.This study used qualitative approach since the data were collected in the form of words. The design of this study was content analysis since it analyzed utterances produced by male and female students. Ten 7th semester students that consist of five males and five females were chosen based on certain criteria in which they are students majoring in linguistic that have done Pragmatics course in the fifth semester and come from different classes. The data were collected through a written Discourse Completing Task (DCT). The data were analyzed by classifying the types of refusal utterances produced by both male and female students based on FelixBrasdefer’s(2008) and using Wardhaugh’s (2006) theory to analyze the possible factors thatinfluence the differences in the use of refusal strategies by males and females.This study found that male and female students used different refusal strategies. All males tend to use reason/explanation strategy as many as 38 times whereas all females mostly used regret/apology strategy for 36 times toward their friends. The possible factors that influence the differences of the use of refusal strategies that male students use categorical statements to refuse some requests, offers, invitations and suggestion toward their friends. Meanwhile female students tend to involve their feeling and tended to maintain solidarity toward their friends by expressing their regret in refusing requests, offers, invitations and suggestion.The writer suggests that next researchers investigate refusal strategies from some different aspects such as age and power relation in using Bahasa Indonesia. They can also use different object, theory and method for their researches.